Contemporary art, capitalization and the blockchain: On the autonomy and automation of art's value - Laura Lotti (Finance and Society, 2016)
This article addresses contemporary art as a means to investigate how, and to what extent, financial logic impacts upon the socio-cultural sphere. Its contribution is twofold: on the one hand, the article shows that contemporary art's valuation practices increasingly reflect the logic of capitalization; on the other hand, it assesses the emancipatory potential of blockchain technology for the cultural sphere. In relation to the latter I argue that, in spite of the technological novelty of blockchain-based art projects, these nonetheless fail to challenge a received logic of finance. This exposes the limitations to technological determinism as a means of countering financial power in the socio-cultural sphere, and points to new problems for art's valuation methods in relation to the liquid logic of algorithmic finance.
Keywords: 300; Contemporary art; valuation; capitalization; computation; blockchain